PERBANDINGAN ABNORMAL RETURN DAN LIKUIDITAS SAHAM PADA PERISTIWA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN INDONESIA TAHUN 2014 (EVENT STUDY SAHAM- SAHAM LQ45 DAN PEFINDO25) - B11111006, William Wendy Ary (Jurnal Manajemen Update, 2015)
This research tries to analyze the effect of Indonesian president and vice-president election towards stocks liquidity and market reaction in Indonesia. Indicators in this study are the abnormal return and bid-ask spread. The samples in this study are both LQ45 index and PEFINDO25 index that actively traded on the June 25, 2015 (t-10) until July 23, 2015 (t+10). The data in this study are secondary data which consists of daily closing prices, Jakarta Composite Index (JSI) daily data, and daily Bid-offer data. The tools of this analyze using t-test and paired samples t-test. T-test results in LQ45 indicates that the abnormal returns are positive and significant on t-5, t-4, t-2, t + 5, and t + 7 t and on the PEFINDO25 there are also positive abnormal returns and significant on t-8, t + 5, t + 7, and t + 10. The test results of paired sample t-test on abnormal stock returns of LQ45 and PEFINDO25 found that there were no significant difference in the time before and after the event of Indonesian elections. The test results of paired sample t-test on the bid-ask spread LQ45 also found that there was no significant difference in the time before and after the event in LQ45, but the bid-ask spread is significant in PEFINDO25. Keywords : Â  Abnormal return, bid-ask spread, paired sample t-test, Indonesian president and vice-president election